(untitled) (South East Asia Journal of Public Health, 2017)
Dog bites in human are a serious public health problem and have been well documented worldwide. As rabies is not a notifiable disease in India and most deaths occur in rural areas where surveillance is poor. The objective of this study to assess the drug prescription patterns of referral cases of dog bite attending in the anti-rabies clinic (ARC) of Department of Community Medicine at MKCG Medical College. For this particular study 606 prescriptions were collected over a six months period. Suspected referred dog bite cases to ARC and willing to participate in the study were included as study subjects. Prescriptions Patients’ identity (name, age, sex) and date of prescription were present in all cases, address was written correctly in only 30% cases. 88% of the prescriptions were legible. Majority prescriptions (44%) were referred from of primary health centers and community health centers. Nearly one third of referred patients had not received anti rabies vaccine. Only 5% cases were administered with rabies immune globulin and about 30% had taken oral antibiotics which were referred from PHCs/CHCs. Specific treatment to dog bite (i.e. use of vaccine & RIG) was lacking in the prescription whereas Co-prescription of other drugs (i.e. antibiotics, pain killers, vitamins) were mentioned in the prescription. Regular prescription auditing with training of Medical Officers on essential drug availability should be undertaken by the Govt. of Odisha in order to give rationality to all prescriptions. South East Asia Journal of Public Health Vol.7(1) 2017: 51-54